Pendidikan Pemuda dalam Perspektif Al Qur'an dan Hadits Tarbawi - Sukmawati, Sri; Rahendra, Maya (Dirosah Islamiyah, 2026)
Youth are a crucial asset and transformative subjects that determine the direction of national and religious civilization. In the contemporary era, the younger generation faces the challenges of digital disruption, a crisis of role models, information overload, and mental health vulnerabilities (quarter-life crisis). This study aims to explore the concepts, methods, and relevance of youth education from the perspective of the Qur'an and Hadith Tarbawi to address these modern challenges. The research method employed is library research, utilizing a thermistic and comparative analysis approach toward classical and contemporary exegeses (tafsir). The results indicate that the Qur'an uses specific terms such as fityah, dzurriyah, and fata to describe the ideal youth who possess integrity, critical thinking, and steadfastness of faith, as represented in the stories of Ashabul Kahfi and Prophet Ibrahim AS. In the perspective of Hadith Tarbawi, Prophet Muhammad SAW emphasized the urgency of optimizing youth through a prophetic pedagogical approach that integrates spiritual intelligence (muraqabah) with the mastery of knowledge. Youth education in Islam must be mutakāmil (integral) by harmonizing the realms of heart, mind, and action through methods of role-modeling (qudwah), advice (mau’izhah), habituation (’âdah), and digital piety. This character-based educational reconstruction aligns with Thomas Lickona's theory, which emphasizes the aspects of knowing, desiring, and doing the good. This study concludes that strengthening the spiritual connection with Allah SWT and integrating the values of the Qur'an and Hadith serve as the primary preventive-curative strategy in safeguarding the religious identity and mentality of youth in the digital age.